KECEMASAN IBU HAMIL DALAM MASA PANDEMI COVID-19 DI WILAYAH KERJA PUSKESMAS MINAS - Nike Puspita Alwi; Ainil Fitri; Winnie Astari (Institut Kesehatan dan Teknologi Al Insyirah, 2021)
Covid-19 still be a pandemic in Indonesia since two years ago. The vulnerable age group are the elderly, the people who has comorbid condition and pregnant woman. Pregnancy will be risk to worsen symptoms and also to maternal and the fetus health. This study aims to describe about the anxiety of Maternal Pregnancy during pandemic Covid-19. The design of this study is descriptive. The population of this study is 98 of pregnant woman who settle in Minas Public Health Center Work Area. The sample was chosen by total sampling technique. Data were collected by using HARS (Hamilton Anxiety Rating Scale) questionnaire. The result finding showed that there are 18,4% respondents didn’t anxiety, 54,1% mild anxiety, 27,6% moderate severity of anxiety, and no respondents has severe or panic (an overwhelm anxiety severity) during Covid-19 Pandemic. We can conclude that Covid-19 in fact brought mild severity to pregnant woman. Minas Public Health Center should give health education about guidelines for pregnancy in pandemic and also how to control the worries pregnancy and health during Covid-19.